Quaternionic Version of Rotation Groups - Rahmawati, Latief; Ardhi Khalif, Muhammad; Farchani Rosyid, Muhammad (Journal Of Natural Sciences And Mathematics Research, 2015)
Quaternionic version of rotation group SO(3) has been constructed. We constructa quatenionic version of rotation operation that act to a quaternionic version of aspace coordinate vector. The computation are done for every rotation about eachcoordinate axes (x,y, and z). The rotated quaternionic space coordinate vector con-tain some unknown constants which determine the quaternionic rotation operator.By solving for that constants, we get the expression of the quaternionics versionof the rotation operator. Finally the generators of th